Analysis of Mathematic Understanding Ability of Senior High School Students on Trigonometric Materials - Arialis Senita (Journal of Research on Mathematics Instruction (JRMI), 2021)
Mathematics has an important role in other branches of science such as physics, chemistry, economics, and others. Through mathematics, students are trained to have a mathematical understanding which will be the basis for creating problem-solving abilities. Although online learning is also balanced with many accesses to get additional deepening of material through internet media, in reality, students cannot digest all the knowledge provided through the internet media. From the difficulty of understanding this learning, the impact is that students have difficulty developing mathematical understanding abilities, which affects student learning outcomes. There is a need to increase the ability of mathematical understanding. The purpose of this study is to describe the students' mathematical understanding ability on Trigonometry material with indicators that will be described are indicators of instrumental understanding and relational indicators. Furthermore, it will be seen which indicators the most problems experienced by students. The method used is descriptive qualitative. The data was obtained from the test answers of class XI students in description questions. From the results of data analysis, it was concluded that students had low abilities in relational understanding indicators.